Which market? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Review of market information systems in Botswana, Ethiopia, Ghana and Zimbabwe - Study report, P Robbins. CTA. 2000. 83pp. ISBN 92 9081 2303 CTA number 982. 10 credit points